Sustainable Indigenous Orchards: An Agroforestry Project in the Colombian Amazon - Shigematsu, Jorge; Sadowski, Sylvia Garcia (Consilience, 2013)
In 2010, NGOs Green Hope Colombia and Forestever started the development of an agroforestry project in the Colombian Amazon. Jorge Shigematsu, the director of Green Hope Colombia, who had been doing social work with indigenous communities in this region since 2007, witnessed how lands in the area had been subjected to indiscriminate tree cutting and light-burn agriculture, resulting in land degradation, loss of biodiversity, food scarcity and displacement of agricultural activities for illegal hunting and animal trafficking. Eventually, these practices would result in the destruction of parts of the region’s Amazon forest. Jorge reasoned that investing in education about sustainability would become essential to protect the forest and to rescue the land and people’s cultural values and traditions. He met Maikov Dumas, a French agro-development engineer and director of NGOs Forestever and Up2Green. They partnered to execute the Sustainable Indigenous Orchard Reforestation Program, which by the end of 2012 had achieved planting of twenty thousand (20,000) native species trees. Their work will serve as a case study for research on economic development and sustainability in indigenous communities, educational outreach and relations between state and indigenous governments. It also provides a perspective on the question of how to approach and balance potential conflicts between ancient indigenous practices and environmental and social sustainability.